Leveraging food security with food aid: the role of applied policy research - Haddad, Lawrence J. (African Journals Online, 2001)
The paper considers that food aid must not only contribute directly to food security; it must be used, wherever possible, to contribute to development. Food aid has now become a scarce resource; it must therefore be used to make a bigger impact on food and nutritional security through better management at the implementation level, donor level and through regional integration. The paper analyses on how far the role of food aid will be redefined in the new millenium.